KUALITAS PELAYANAN, HARGA, KEPERCAYAAN TERHADAP LOYALITAS MELALUI KEPUASAN JNE: Studi Kasus Masyarakat Rw 06 Kelurahan Bambu Apus - Fenni Aulia Agusta, - (2019)
This research is a quantitative research that aims to determine the effect of service quality, price, trust on loyalty through satisfaction as an intervening variable. The population in this study was the community of RW 06, kelurahan Bambu Apus. The sample size was taken as many as 100 respondents, with non probability sampling method, especially purposive sampling. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis. The results of this study indicate that (1) Service quality does not have a direct and not significant effect on loyalty with the path coefficient value of 0.101. (2) Service quality does not affect loyalty through satisfaction as an intervening variable with a path coefficient of 0.003.(3) Price has a significant effect on satisfaction with the path coefficient value of 0.281. (4) Price has a significant indirect effect on loyalty through satisfaction as an intervening variable with a path coefficient of 0.106. (5) Trust has a direct and significant effect on loyalty with a path coefficient of 0.481. (6) Trust has an indirect significant effect on loyalty through satisfaction as an intervening variable with a coefficient of 0.209.